Адаптивна стратегія розподілу буфера у вузлах телекомунікаційних мереж - Ponomarenko, L. A.; Melikov, A. Z.; Feyziyev, V. Sh. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Approximate formulae are obtained to calculate the cell loss probability for packets of different types in ATM networks with limited partial buffer sharing strategy. A new approach to solution of the problem of calculating characteristics of this strategy quality, based upon principles of state phase-aggregation theory, is offered. The results of numerical experiments performed by using the developed formulae are given.